Exacting Responses: Lack of Endocrine Cephalic Phase Responses Upon Oro-Sensory Exposure - Lasschuijt, Marlou P.; Mars, Monica; de Graaf, Cees; Smeets, Paul A. M. (Frontiers in Endocrinology, 2018)
Oro-sensory exposure to food plays an important role in the regulation of food intake. One proposed underlying mechanism is the occurrence of cephalic phase responses (CPRs). CPRs include the pre-digestive endocrine responses induced by food related sensory input. Yet, whether oro-sensory exposure duration or sweetness intensity affects CPRs is unknown. The objective of this study was to determine the independent and interactive effects of oro-sensory duration (chewing) and stimulation intensity (sweetness) on endocrine CPRs and satiation. Eighteen males (22±2 y, BMI 22±2 kg/m2) participated in a 2x2 randomized study with a control condition. Each session participants performed modified sham feeding (MSF) with one of four gel-based model foods. During the control session no MSF was performed. Model foods differed in chewing duration (hard or soft texture) and sweetness (low or high intensity). During each session eight blood samples were collected up till 25 min after MSF onset. Subsequently, food intake from an ad libitum lunch was measured. No typical cephalic phase response was found for insulin, PP and ghrelin. However, the overall PP response was 1.1 times greater for the hard sweet MSF condition compared to control (p=0.02). Overall ghrelin responses were 1.1 times greater for the hard model food compared to the soft model food conditions (p=0.003). These differences in endocrine response were not associated with differences in food intake at the subsequent meal. Exploratory sub analysis of the responsive insulin curves showed that after 2.5 minutes of MSF the hard texture model foods insulin concentrations were 1.2 greater compared to the soft texture. These findings indicate that texture hardness and sweetness increase the overall PP response and that MSF on hard texture increases the overall ghrelin response compared to soft texture model foods. However, MSF on model foods does not lead to a typical cephalic phase response. This study, among others, shows that there are major dissimilarities in the endocrine responses to food stimulation between individuals. This emphasizes the importance of considering cephalic responders and non-responders. More research is needed to understand CPRs in relation to food texture and taste properties.